2006
DOI: 10.1029/2006gl027795
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake magnitude estimation from peak amplitudes of very early seismic signals on strong motion records

Abstract: [1] We show that the low-pass filtered, peak amplitudes of initial P-and S-wave seismic signals recorded in the vicinity of an occurring earthquake source correlates with the earthquake magnitude and may be used for real-time estimation of the event size in seismic early warning applications. The earthquake size can be therefore estimated using only a couple of seconds of signal from the P-or S-wave onsets, i.e. while the rupture itself is still propagating and rupture dimension is far from complete. We argue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
168
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(176 citation statements)
references
References 17 publications
6
168
1
1
Order By: Relevance
“…The ability to correctly distinguish a small shock from a large event through the analysis of the first P-wave observation is crucial for risk mitigation actions triggered by earthquake early warning systems. Several authors demonstrated that the early portion of recorded P-waves contains information regarding the magnitude through its frequency content and/or amplitude [17][18][19][20] . Most of these studies concentrated on the analysis of a fixed P-wave time window (PTW; 3-4 s).…”
mentioning
confidence: 99%
“…The ability to correctly distinguish a small shock from a large event through the analysis of the first P-wave observation is crucial for risk mitigation actions triggered by earthquake early warning systems. Several authors demonstrated that the early portion of recorded P-waves contains information regarding the magnitude through its frequency content and/or amplitude [17][18][19][20] . Most of these studies concentrated on the analysis of a fixed P-wave time window (PTW; 3-4 s).…”
mentioning
confidence: 99%
“…If four seconds of P-wave data is being used, and the duration of an M 6.5 earthquake is four seconds, can P-wave parameters distinguish an M 7.5 earthquake from an M 6.5 event? There is clear evidence that the amplitude of the P wave within the first few seconds does saturate for M > ~7 earthquakes (Zollo et al 2006;Wurman et al 2007;Murphy and Nielsen 2009;Brown et al 2009, this issue). To try to reduce this problem, several methodologies use longer time windows of the P wave and/or the S wave to update magnitude estimates (Zollo et al 2006;Kamigaichi et al 2009, this issue).…”
Section: Using the P Wavementioning
confidence: 94%
“…There is clear evidence that the amplitude of the P wave within the first few seconds does saturate for M > ~7 earthquakes (Zollo et al 2006;Wurman et al 2007;Murphy and Nielsen 2009;Brown et al 2009, this issue). To try to reduce this problem, several methodologies use longer time windows of the P wave and/or the S wave to update magnitude estimates (Zollo et al 2006;Kamigaichi et al 2009, this issue). When using the frequency content of the P wave there is less empirical evidence for saturation (Kanamori 2005;Olson and Allen 2005;Lewis and BenZion 2008;Brown et al 2009, this issue), although this conclusion is controversial (Rydelek and Horiuchi 2006;Yamada and Ide 2008), and a satisfactory physical explanation remains elusive.…”
Section: Using the P Wavementioning
confidence: 94%
See 1 more Smart Citation
“…These algorithms require the seismic waveforms either from a single seismic sensor (the so-called on-site warning systems; e.g., Wu and Kanamori, 2005;Kanamori, 2005;Zollo et al, 2006;Böse et al, 2007) or from a seismic network or subnetwork (the so-called regional warning systems; e.g., Wu and Teng, 2002;Allen and Kanamori, 2003;Cua and Heaton, 2007). On-site and regional warning approaches deliver estimates of source and ground-motion parameters with different speed and accuracy (e.g., Kanamori, 2005).…”
Section: Introductionmentioning
confidence: 99%